Anti-diabetic properties of prickly pear cactus - Trejo-Gonzalez, A.; Calva, E.; Monterubio, P. J.; Hernandez, R.; Sanchez, L.; Terrazas, J.; Raida, M. A.; Cobos, B. (Journal of the Professional Association for Cactus Development, 2021)
Pre-Columbian medicine entailed the succesfull use of native medicinal plants for effective therapeutic treatment of disease, such as Diabetes Mellitus.